CFD Simulation Study of Water Sleeve Tray for Erosion - Xue CHEN; Chunli ZHAO; Feng LIU; Zhongshuo LIU; Haoran TANG; Ziyuan LIU1 (Liaoning Shiyou Huagong Daxue xuebao)
In the process of oil and gas field production, as well as in the gathering and transportation phases, the water jacket furnace coil serves as a crucial component for natural gas heating, playing a significant role in both heating and energy support. However, the presence of fine grit within the water jacket furnace coils can result in erosion damage that is challenging to predict. Therefore, it is essential to understand the factors influencing the erosion of water jacket furnace coils and to establish an effective predictive model. This study employs computational fluid dynamics (CFD) simulations and sensitivity analyses to investigate the effects of temperature, pressure, gas flow rate, particle diameter, bend diameter, and curvature radius on the erosion of water jacket furnace coils. The results indicate that the gas flow rate, particle diameter, bend diameter, and curvature radius are the primary factors affecting erosion. Consequently, a comprehensive erosion prediction model is developed, providing a scientific basis for equipment maintenance and safety management. The findings of this study offer a vital reference for addressing the erosion issues associated with water jacket furnace coils and hold practical significance in engineering applications.